Mindfulness Based Cognitive Therapy dalam Menurunkan Kecemasan Praanestesi Pasien Appendiktomi di Ruang Dahlia RSUD dr. T. C. Hillers Maumere - Maria Rosalinda Dua Bala; Maria Fransiska Ronalia (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Introduction: Appendectomy is a relatively safe surgical procedure. One important aspect of this stage is maintaining the patient's mental stability, especially before administering anesthesia. However, anesthesia often causes anxiety in patients. Mindfulness-based cognitive therapy has been shown to significantly improve quality of life by minimizing anxiety. Objective: This study analyzed the effect of Mindfulness-based cognitive therapy (MCT) in reducing pre-anesthetic anxiety in appendectomy patients. Methods: This study used a case study design with a nursing care process approach. The subjects in this case study were two patients who met the inclusion criteria. The instrument used was an observation sheet according to the Indonesian Society for Anesthesia and Clinical Trials (SLKI). Results: The results of the case study showed that both patients experienced pre-anesthetic anxiety. After receiving Mindfulness-based cognitive therapy, pre-anesthetic anxiety decreased. Conclusion: This case study demonstrated that pre-anesthetic anxiety decreased after Mindfulness-based cognitive therapy.